(Invited) Pore Filling of Porous Silicon with Ferromagnetic Nanostructures. (18th September 2015) - Rumpf, Klemens; Granitzer, Petra; Poelt, Peter; Michor, Herwig
Abstract : Within this work the deposition of ferromagnetic metals in high aspect ratio mesopores will be elucidated regarding the specific nucleation and growth of the deposited nanostructures under various conditions. Since mesoporous morphologies offer dendritic pore walls these structural inhomogeneities of the matrices are critical for the deposition process. Experiments show that the nucleation preferentially starts at the "tops" of the rough surface. A further key point of the presentation is the magnetic characterization of the various nanocomposites. Magnetic characterization of the systems shows that not only the morphology of the deposited metal structures (size, shape, distribution) determines the magnetic properties but also the morphology of the template (side-pore length). In this sense magnetic coupling between the nanostructures plays a crucial role and is strongly influenced by morphological parameters. From all these findings it is possible to prepare samples with specific magnetic properties which could be of interest for on-the-chip devices.